Monetary Policy Rules in Emerging Countries: Is there an Augmented Nonlinear Taylor Rule? - Guglielmo Maria Caporale; Abdurrahman Nazif Catik; Mohamad Husam Helmi; Faek Nemla Ali; Coskun Akdeniz (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the Taylor rule in five emerging economies, namely Indonesia, Israel, South Korea, Thailand, and Turkey. In particular, it investigates whether monetary policy in these countries can be more accurately described by (i) an augmented rule including the exchange rate, as well as (ii) a nonlinear threshold specification (estimated using GMM), instead of a baseline linear rule. The results suggest that the reaction of monetary authorities to deviations from target of either the inflation or the output gap varies in terms of magnitude and/or statistical significance across the high and low inflation regimes in all countries. In particular, the exchange rate has an impact in the former but not in the latter regime. Overall, an augmented nonlinear Taylor rule appears to capture more accurately the behaviour of monetary authorities in these countries.
Keywords: C13; C51; C52; E52; E58; 330; Taylor rule; nonlinearities; emerging countries